(untitled) (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
This article presents some thoughts on the concept of creativity, its innateness in a person, the positive impact of creativity on the educational process, its study by scientists, and the specificity of preparing students of pedagogical education for creative activity.